2000
DOI: 10.1046/j.1365-3016.2000.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the prevalence of persistent otitis media with effusion in one‐year‐old infants

Abstract: The objective of this population-based cohort study was to evaluate the prevalence of persistent otitis media with effusion (OME) and its seasonal variation in 12-month-old infants. All 30099 infants born in the eastern part of The Netherlands between 1 January 1996 and 1 April 1997 were invited for hearing screening, comprising a protocol of three possible tests. Those who failed all three screening tests were referred to an ENT clinic for examination. Prevalences (i.e. the probability that a child would fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
1
15
1
Order By: Relevance
“…After the age of seven years old, the prevalence falls from 6.8% to 5% [15]; our results confirm data literature. In our study the distribution of the case in relation to season was different, in which the patients with OME were higher in the winter as opposed to the summer months which was consistent with other studies [11,23,24], this was probably due to increased frequency of upper respiratory tract infection during winter months. The study demonstrated that OME in West Baghdad is slightly more among boys (54.4%) than girls (45.6%); this is comparable with some studies which gave no significant difference in the prevalence of OME between both genders [25], even if the literature data are discordances because some studies demonstrate that males have a significantly higher proportion of OME (p<0.001) while others founds that the number of girls with OME significantly exceeds the number of boys with OME (<chi>2=7.384, P=0.0067) [17,26].…”
Section: Discussionsupporting
confidence: 91%
“…After the age of seven years old, the prevalence falls from 6.8% to 5% [15]; our results confirm data literature. In our study the distribution of the case in relation to season was different, in which the patients with OME were higher in the winter as opposed to the summer months which was consistent with other studies [11,23,24], this was probably due to increased frequency of upper respiratory tract infection during winter months. The study demonstrated that OME in West Baghdad is slightly more among boys (54.4%) than girls (45.6%); this is comparable with some studies which gave no significant difference in the prevalence of OME between both genders [25], even if the literature data are discordances because some studies demonstrate that males have a significantly higher proportion of OME (p<0.001) while others founds that the number of girls with OME significantly exceeds the number of boys with OME (<chi>2=7.384, P=0.0067) [17,26].…”
Section: Discussionsupporting
confidence: 91%
“…However, most infants who repeatedly fail a distraction hearing screen have conductive hearing loss due to OM [15, 47, 48]. A previous study [15] reported that 58% of the children failing the CAPAS and referred to an ENT department were diagnosed with bilateral OME and 70% with bilateral or unilateral OME, as confirmed by otoscopy and tympanometry at the ENT department.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 However, as our study is a birth cohort study in which the participants were seen at scheduled follow-up visits, all seasons are represented so that information bias due to a seasonal effect will be minimal.…”
Section: Discussionmentioning
confidence: 99%